Implementasi Agile Development Dengan Scrum Dalam Perancangan Sistem Informasi Berbasis Website - Pratama, Elan; Nur’aini (LPPM STMIK IKMI Cirebon, 2023)
A website is a must-have information tool for business owners. This can be a promotional medium for the company to make it look professional so potential consumers can find out its background. CV Sumber Teknik is a start-up company engaged in electronic repair service in Indramayu. This company needs promotional media with coverage throughout the wider Indramayu area, with a company profile website that can be a source of information and good service for consumers. In building this information system, researchers include system analysis. This system uses the Agile Software Development methode with the scrum framework. The Scrum method is the suitable medium for building an interactive website-based information system using the Laravel 8 framework and the Xampp/Mysql database and testing the system using black box testing. The results of this research in creating a web-based information system were successfully achieved quickly because the work process used Scrum, which had maximum results.